The influence of the hardness of the shaft journals and the chemical composition of tribotechnical organic-inorganic materials for forming coatings on steel on the performance properties of crankshaft bearings marine medium speed diesel engines (Far Eastern Federal University: School of Engineering Bulletin, 2024)
The paper summarizes the results of studies of the operational properties of the tribo-tension "crank-shaft – bearing liner" of a marine medium-speed diesel engine. The main cause of crankshaft failures is the wear of the necks. To increase the durability of crankshaft bearings, it is proposed to form wear-resistant thin-film metal-ceramic coatings on the shaft necks, which are obtained by tribomechanical modification of the surface with organo-inorganic materials based on vermiculite.It has been established that the following factors affect the wear rate of the parts of the tribo-tension "crankshaft – bearing liner" of a marine medium-speed diesel engine: mechanical properties: the modulus of elasticity of the surface layer has the greatest influence. To increase the wear resistance of the parts of the tribo-tension "crank-shaft – bearing liner" and, accordingly, its durability, it is necessary to form thin-film metal-ceramic coatings on the surface of the necks, providing optimal parameters of mechanical properties and surface structure.